A transversal description of job insecurity in Mexican professionals, 1995-2018. - Mejía-Reyes, Carlos (2022)
Job insecurity, understood as the perception of objective and subjective vulnerability in which the subjects are found in terms of participation or permanence in a job, forms an inherent feature of contemporary global capitalism in which flexibility and precariousness prevail to define the epoch. This condition affects the total number of work activities, but coexists with a story that points to academic training as a guarantee of reducing the fear of the loss of the source of income in agents who achieved professional studies and who are inserted in functions according to their instruction. Thus, the Job insecurity is presumed to be lower in professionals compared to agents in different occupational conditions. This document aims to descriptively explore the Job insecurity in Mexican informants with professional activities of the Latinobarometer survey from 1995 to 2018 in a transversal way to identify specific trends in specific time spaces characterized by economic phenomena and the latest cycle is analyzed on an ad hoc basis in its trends against other types of employment.